2012
DOI: 10.1016/j.mayocp.2011.12.016
|View full text |Cite
|
Sign up to set email alerts
|

High School Football and Risk of Neurodegeneration: A Community-Based Study

Abstract: Objective: To assess whether high school football played between 1946 and 1956, when headgear was less protective than today, was associated with development of neurodegenerative diseases later in life. Methods: All male students who played football from 1946 to 1956 in the high schools of Rochester, Minnesota, plus a non-football-playing referent group of male students in the band, glee club, or choir were identified. Using the records-linkage system of the Rochester Epidemiology Project, we reviewed (from Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 20 publications
3
88
0
1
Order By: Relevance
“…The total number of NFL players who had a neurodegenerative disease at the time of death was small, and the increased rate of neurodegenerative disease could have been related in part to the reduced mortality from other causes. In contrast, in a study of former high school football players (who played from 1946-1956), there was not an increased risk of later developing dementia, Parkinson's disease, or ALS compared with non-football-playing high school males (Savica et al, 2012). Therefore, at present, the risk for developing a neurodegenerative disease in former athletes who played football or other contact sports is unclear.…”
Section: Directions For Future Researchmentioning
confidence: 90%
“…The total number of NFL players who had a neurodegenerative disease at the time of death was small, and the increased rate of neurodegenerative disease could have been related in part to the reduced mortality from other causes. In contrast, in a study of former high school football players (who played from 1946-1956), there was not an increased risk of later developing dementia, Parkinson's disease, or ALS compared with non-football-playing high school males (Savica et al, 2012). Therefore, at present, the risk for developing a neurodegenerative disease in former athletes who played football or other contact sports is unclear.…”
Section: Directions For Future Researchmentioning
confidence: 90%
“…The neurodegenerative mortality rate of the NFL cohort was reported to be 3-times higher than that of the general population and the rate of Alzheimer's dementia and amyotrophic lateral sclerosis (ALS) in particular was 4-times greater in the NFL cohort. Conversely, in a 2012 study of 438 Minnesota high school football players who competed between 1946-1956, there was no increased risk of Alzheimer's disease, ALS or Parkinson's disease when compared with a control group of 140 individuals who participated in band, glee club or choir [31]. Thus, the limited data to date reveals one survey and two epidemiological studies indicating a higher rate of dementia in professional (but not in high school) football players.…”
Section: Epidemiologic Studies Of Ctementioning
confidence: 90%
“…32 The single epidemiologic study of high school football players found no risk increase for degenerative disease due to football. 28 Finally, the risk for catastrophic brain injury in football is actually lower than for many common, everyday activities.…”
Section: Discussionmentioning
confidence: 99%